SPONTANEOUS PERFORATION OF MECKEL’S DIVERTICULUM PRESENTING WITH GENERALIZED PERITONITIS - Ullah, Faizan; Raza, Zeeshan; Nehal, Faizan (Journal of Ayub Medical College Abbottabad, 2020)
Meckel’s diverticulum is the most common congenital anomaly of the GIT with a low incidence of 2% and the complication rate is even lower with perforation being the rarest. We report an intriguing case of a 15-year-old male, who presented with one-week history of high-grade fever and diarrhoea followed by acute onset of abdominal pain in the periumbilical region which became generalized. On physical examination his abdomen was distended with guarding and rigidity. A provisional diagnosis of peritonitis secondary to enteric perforation was made and exploratory laparotomy was done which revealed a perforated Meckel’s diverticulum and advanced peritonitis. A diverticulectomy with double barrel ileostomy were performed. No heterotopic tissue in the diverticulum was noted on histopathology, nor any other abnormal tissue identified. The patient made an uneventful recovery postoperatively and ileostomy reconstruction was done two months later. This case report is rare case of Meckel’s diverticulum complications and highlights the importance of considering Meckel’s diverticulum as a differential diagnosis in every patient presenting with acute abdomen, which can aid toward better management through laparoscopy. Keywords: Diverticulum; Meckel’s diverticulum; Laparotomy; Peritonitis; Ileostomy; Idiopathic